MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMA DHARMA KARYA UT PONDOK CABE ILIR - Nurjamil; Sadam, Khoirul; Maulana, Azis; Hasanah, Yenny Marinatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of educational facilities and infrastructure in supporting the quality of the learning process at SMA Dharma Karya UT Pondok Cabe Ilir. The scope of this research covers five stages of the management cycle: planning, procurement, inventory, maintenance, and disposal. This study uses a descriptive qualitative approach, with data collected through in-depth interviews, direct observation, and document study. The results show that: (1) facility planning is carried out based on a needs analysis and priority scale; (2) procurement of facilities is sourced from foundation funds, government assistance, donors, and community contributions; (3) asset inventory has been carried out systematically through a coding mechanism and structured master record-keeping; (4) facilities are optimally utilized daily to support the learning process, accompanied by routine and periodic maintenance to reduce asset depreciation; and (5) disposal of facilities and infrastructure is carried out through a formal procedure involving a foundation verification team to ensure accountability and budget efficiency. These findings indicate that the school has implemented a systematic and accountable facility management cycle that effectively supports the learning process.